Supporting Students' Understanding of Percentage - Veronika Fitri Rianasari; I Ketut Budaya; Sitti Maesuri Patahudin (Journal on Mathematics Education, 2012)
Many researches revealed that pupils often find difficulties to understand percentage although they are able to recite percent as per hundred and carry out the computations correctly. This might happen due to the way in which the learning percentage has been taught that tends to focus on procedures and recall instead of getting a real understanding of percentage. In Realistic Mathematics Education approach, in which the basic concept is rooted from Freudenthals' idea, mathematics is the activity of organizing matter from reality. Therefore, mathematics should be experientially real for the students. Consequently, in this research the instructional activities were designed through exploring some contextual situations in which percentages play role. Therefore, this research aimed to develop a local instructional theory to support students to extend their understanding of percentage. This research used design research method as an appropriate means to achieve the research aim. The research involved students and mathematics teachers of grade 5 in SD Laboratorium UNESA and SD BOPKRI III Demangan Baru Yogyakarta. Keywords: design research, percentage, understanding, contextual situations